2018
DOI: 10.1108/pijpsm-01-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Police integrity in China

Abstract: Purpose The purpose of this paper is to examine the contours of police integrity among Chinese police officers. Specifically, this study explores how Chinese police evaluate integrity based on official policy governing interactions, discipline governing infractions, views of seriousness, and willingness to inform when others engage in misconduct. Design/methodology/approach In total, 353 police officers were surveyed representing those attending in-service training program at a Chinese police university in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…It was also reported that in the single year of 2017, the public security police agencies nationwide investigated 10,390 cases of police misconduct involving the violation of law or administrative disciplines (Dai, 2018). Explanations for this vary, with some scholars (e.g., G. Wu et al, 2018) suggesting some portion of this increase is a greater willingness to use the system, suggesting that police misconduct may not have necessarily increased.…”
Section: Policing In Chinamentioning
confidence: 99%
See 4 more Smart Citations
“…It was also reported that in the single year of 2017, the public security police agencies nationwide investigated 10,390 cases of police misconduct involving the violation of law or administrative disciplines (Dai, 2018). Explanations for this vary, with some scholars (e.g., G. Wu et al, 2018) suggesting some portion of this increase is a greater willingness to use the system, suggesting that police misconduct may not have necessarily increased.…”
Section: Policing In Chinamentioning
confidence: 99%
“…Many of these studies used the integrity scale (involving 11 scenarios) developed by Klockars et al (2000). As scholars have noted, while previous research has documented some common patterns regarding police integrity across nations, for instance, the existence of the code of silence among officers in both developed and developing nations, studies also suggest that police officers from different countries vary in their perceptions of police integrity scenarios (G. Wu et al, 2018).…”
Section: Determinants Of Police Integrity: a Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations